Impact of floating platforms on the limnological aspects of hydropower plant reservoirs - Vanzela, L. S.; Pereira, D. C.; Lima, L. D. S. C.; Khan, K. U. [UNESP]; Mansano, C. F. M. (Iran Solid Waste Assoc, 2020)
Floating platforms at the hydropower plant reservoirs are attractive sites for aquaculture, fishing and other recreational activities. However, the unregulated construction of these platforms may negatively affect the fauna, flora and water quality of reservoirs. Thus, this study aimed to evaluate the impact of floating platforms on the limnological aspects of Nova Ponte hydropower plant reservoirs at the Center-West of Minas Gerais State of Brazil. The obtained data were analyzed using the correlation and regression analysis. Dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, total coliforms and thermotolerant bacteria were plotted against the density of floating platforms. The density of platforms significantly (p-value > 0.05) impacted the analyzed limnological aspects of reservoirs. Based on the present results, 4 floating platforms/km(2) (1 platform per 25 hectares) of surface water should be the maximum density in order to avoid the deterioration of water quality of reservoirs. With 4 platforms/km(2), the expected values in fishing period were estimated to be 5.4 mg/L for biochemical oxygen demand, 375 most probable number per 100 mL of sample for thermotolerant bacteria and 6.1 mg/L for chemical oxygen demand. In fishingban period, the expected values were estimated to be 4.1 mg/L for dissolved oxygen, 3.4 mg/L for biochemical oxygen demand, 379 most probable number per 100 mL of sample for thermotolerant bacteria and 4.2 mg/L for chemical oxygen demand. This finding provides important base-line information which could help policy makers to take effective measurements for the appropriate management of surface water resources. (C) 2020 GJESM. All rights reserved.
Keywords: Aquaculture; diffused pollution; Recreational activities; Sustainable environment; Waterborne diseases; Water management